2004
DOI: 10.1097/01.md.0000133624.65946.40
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thrombocytopenic Purpura and Common Variable Immunodeficiency

Abstract: To describe the main characteristics and outcome of autoimmune thrombocytopenic purpura (AITP) in patients with common variable immunodeficiency (CVID), we analyzed data from 21 patients and reviewed additional cases from the literature. To be included in this study, patients had to have CVID and a previous history of AITP with a platelet count < or = 50 x 10(9)/L at onset. A complete response to treatment was defined by a platelet count > or = 150 x 10(9)/L, and a partial response by a platelet count >>50 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 22 publications
4
102
1
10
Order By: Relevance
“…ITP can be a presenting feature of CVID, in one series of patients with CVID and ITP 17/21 presented with ITP alone. 16 The utility of screening all ITP patients for CVID, however, is unclear.…”
Section: Question: Are There Additional Tests That Can Help Confirm Tmentioning
confidence: 99%
“…ITP can be a presenting feature of CVID, in one series of patients with CVID and ITP 17/21 presented with ITP alone. 16 The utility of screening all ITP patients for CVID, however, is unclear.…”
Section: Question: Are There Additional Tests That Can Help Confirm Tmentioning
confidence: 99%
“…As an example, a study of 21 patients with CVID and immune thrombocytopenic purpura revealed that CVID was diagnosed in only 19% of cases prior to the onset of immune thrombocytopenic purpura (88). Other clinical features associated with PAD can be clues for diagnosis, such as granulomatous disease, splenomegaly, unexplained chronic lung disease, unexplained chronic gastrointestinal disease, or inflammatory arthropathy (32,64,111).…”
Section: Who Should Be Screened For Pad?mentioning
confidence: 99%
“…In most cases, the treatment of autoimmunity in CVID is the same as for immune competent subjects [4,6] with the caveat that when immune suppression is used, lower doses and shorter periods of treatment are advisable, as opportunistic and or fatal complication infections become more likely with prolonged or excessive treatment (Table I). For ITP and AIHA, increased doses of immune globulin may be helpful.…”
Section: Treatment Of Autoimmunitymentioning
confidence: 99%